Learn computer forensics : your one-stop guide to searching, analyzing, acquiring, and securing digital evidence - Oettinger, William (Expert insight., 2022)
Computer Forensics, being a broad topic, involves a variety of skills which will involve seizing electronic evidence, acquiring data from electronic evidence, data analysis, and finally developing a forensic report. This book will help you to build up the skills you need to work in a highly technical environment. This book's ideal goal is to get you up and running with forensics tools and techniques to successfully investigate crime and corporate misconduct. You will discover ways to collect personal information about an individual from online sources. You will also learn how criminal investigations are performed online while preserving data such as e-mails, images, and videos that may be important to a case. You will further explore networking and understand Network Topologies, IP Addressing, and Network Devices. Finally, you will how to write a proper forensic report, the most exciting portion of the forensic exam process. By the end of this book, you will have developed a clear understanding of how to acquire, analyze, and present digital evidence, like a proficient computer forensics investigator.